ANALYSIS OF FOOD DISORDERS PRESENT IN INDIVIDUALS DIAGNOSED WITH AUTISTIC SPECTRUM DISORDER IN ASSISTANCE BY APAE-GOIÂNIA (CIPEEX, 2022)
THE MAIN EATING DISORDERS ARE ANOREXIA AND BULIMIA NERVOSA. IN INDUSTRIALIZED COUNTRIES, THESE CONDITIONS HAVE BEEN OBSERVED EARLY IN LIFE AND HAVE NOT BEEN EXCLUSIVE TO RICH AND WHITE WOMEN, ALTHOUGH THE OCCURRENCE IN FEMALES IS MUCH HIGHER. THESE PATIENTS SHOW EXTREME FEAR OF GAINING WEIGHT, THERE BEING A DISTORTION IN THE IMAGE THEY HAVE OF THEIR OWN BODY. AUTISM IS A BEHAVIORAL SYNDROME THAT RESULTS IN DIFFICULTIES IN SOCIAL INTERACTION, COMMUNICATION AND COGNITION. IN THIS SENSE, SEVERAL CURRENT STUDIES SHOW THE RELATIONSHIP BETWEEN EATING DISORDERS IN PATIENTS WITH AUTISM SPECTRUM DISORDER. THEREFORE, THE OBJECTIVE OF THE STUDY IS TO ANALYZE THE FREQUENCY OF OCCURRENCE OF THESE ASSOCIATED CONDITIONS IN A GROUP OF PATIENTS FROM A HEALTH INSTITUTION IN GOINIA. THIS IS A CROSS-SECTIONAL STUDY THROUGH THE APPLICATION OF THE QUESTIONNAIRE THE SWEDISH EATING ASSESSMENT FOR AUTISM SPECTRUM DISORDERS (SWEAA) IN PATIENTS ASSISTED IN ASSOCIATION OF PARENTS AND FRIENDS OF THE EXCEPTIONAL (APAE). THE QUESTIONNAIRE WILL BE APPLIED TO ALL PATIENTS DIAGNOSED WITH AUTISM SPECTRUM DISORDER, AGED BETWEEN 15 AND 29 YEARS, WITHOUT ANY CHANGES IN INTELLIGENCE. WITH THE DEVELOPMENT OF A QUANTITATIVE ANALYSIS, IT IS EXPECTED TO PROVE THE HIGH PREVALENCE OF THE ASSOCIATION BETWEEN AUTISM SPECTRUM DISORDERS AND EATING DISORDERS, AS WELL AS WHETHER THIS INTERCORRELATION FAVORS CONSIDERABLE COMPLICATIONS IN CLINICAL MANIFESTATIONS. IT IS PROPOSED THAT THE SOCIAL AND EDUCATIONAL IMPACTS BE ESTABLISHED IN THE SHORT TERM, OF INTERINSTITUTIONAL SCOPE, IN THE AREA OF €‹€‹NEUROSCIENCES. AND THAT THROUGH THIS STATISTICAL SURVEY, IT IS POSSIBLE TO ELUCIDATE THE MAIN EXISTING STANDARDS, IN ORDER TO ESTABLISH PREVENTIVE MEASURES, IMPROVING THE QUALITY OF LIFE.
Keywords: Childhood autism. Autisic Disorder. Appetite. Anorexia nervosa.